2021
DOI: 10.1177/02676591211023687
|View full text |Cite
|
Sign up to set email alerts
|

Variability of three activated clotting time point-of-care systems in cardiac surgery: reinforcing available evidence

Abstract: Background: Cardiac surgery with extracorporeal circulation (ECC) requires the administration of anticoagulant drugs to maintain ACT ranges 400–600 seconds, which requires exhaustive coagulation monitoring for which various point-of-care devices are available. However, there is variability between them, so we aimed to compare the values in ACT measurement. Methods: Simultaneous ACT measurements were performed with the Hemochron Response®, Hemostasis Management System Plus® (HMS Plus®) and Hemochron Signature® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Another recent study showed similar results and concluded that the variability of different devices for measurement of ACT should be known and taken into account during clinical practice. 20…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study showed similar results and concluded that the variability of different devices for measurement of ACT should be known and taken into account during clinical practice. 20…”
Section: Discussionmentioning
confidence: 99%